Crise econômica e despedida coletiva: o direito trabalhista brasileiro está apto a enfrentá-las? - Santos, Ariane Joice dos (2010)
With the failure in the capitalist production process and the 2008 world economic crisis, a deceleration in the market occurred with the resulting retraction in product inventory and credit. The economy s globalization has led the internal market to suffer major impacts in view of the cancellation of contracts entered with international companies, resulting in the reduction of costs though collective dismissals of laborers in various companies in our country. By virtue of absence of regulation in article 7, I, of the Federal Constitution which provides on the protection of the employment relationship against the arbitrary dismissal or dismissal without cause and the denunciation of Covenant 158 in the ILO by Brazil the employers class have been dismissing a considerable number of employees without observing any process prior to such act. The result is the discussion on the validity of such dismissals in the labor courts which, based on the normative force of principles, on international guidelines, on comparative law and the constitutionalizing of private law, which have been declared abusive due to non-observance of the duties connected to the general objective good-faith, such as the duty to negotiate and the right to information. There are no doubts that the parties to this relationship should gather for a social dialogue, aiming at creating mechanisms to avoid collective dismissals such as the preparation of autonomous clauses or, in the impossibility thereof, of procedures to be complied with so as to attenuate the social impact, avoiding great unfair actions in such arena. Therefore, there are prerequisites to be overcome in the Brazilian labor law, form the point of view of social efficacy of collective bargaining, either by the fact that the union freedom has not fully reached the free and democratic organization, or by the fact of the persisting normative power of the Labor Justice